The Surprising Features of the TEAD4‐Vgll1 Protein–Protein Interaction. Issue 4 (6th February 2014) - Mesrouze, Yannick; Hau, Jean Christophe; Erdmann, Dirk; Zimmermann, Catherine; Fontana, Patrizia; Schmelzle, Tobias; Chène, Patrick
Abstract The Hippo signaling pathway, which controls organ size in animals, is altered in various human cancers. The TEAD transcription factors, the most downstream elements in this pathway, are regulated by different cofactors, such as the Vgll (vestigial‐like) proteins. Having studied the interaction between Vgll1‐derived peptides and human TEAD4, we show that, although it lacks a key secondary structure element required for tight binding by two other TEAD cofactors (YAP and TAZ), Vgll1‐derived peptides bind to TEAD with nanomolar affinity. We identify a β‐strand:loop:α‐helix motif as the minimal Vgll binding site. Finally, we reveal an unexpected difference between mouse and human Vgll1‐derived peptides.